The impact of strategic alliances on corporate real investment and its mechanisms from the perspective of organizational learning theory: An empirical analysis based on Chinese listed companies - Kai Gao; Xinlei Huang (PLoS ONE, 2025)
This study examines how firms enhance resource allocation efficiency and stimulate real investment through strategic alliances. The findings, based on data from Chinese A-share listed companies on the Shanghai and Shenzhen Stock Exchanges from 2009 to 2022, indicate a significant positive correlation between strategic alliances and corporate real investment. This suggests that strategic alliances effectively improve resource allocation efficiency and promote investment in the real economy. By differentiating between equity-based and bilateral contractual strategic alliances, the results highlight a significantly positive impact of equity-based strategic alliances on corporate real investment. Path analyses further reveal that strategic alliances promote real investment growth by stimulating innovation momentum, enhancing risk-taking capacity, and strengthening innovation capability. Additional analyses indicate that companies with robust capital acquisition abilities—characterized by high commercial credit, patient capital, and government subsidies—can significantly enhance the positive effect of strategic alliances on real investment. This study enriches theoretical discourse on the economic consequences of strategic alliances, and offers policy recommendations for firms to optimize resource allocation and for governments to effectively guide capital toward the real economy.